2005
DOI: 10.1007/s00467-005-2063-x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood microscopic polyangiitis associated with MPO-ANCA

Abstract: We reviewed the clinical, histological and serological parameters of microscopic polyangiitis (MPA) associated with antineutrophil cytoplasmic antibodies (ANCA) specific to myeloperoxidase (MPO). Six girls and one boy aged 12.0+/-2.6 years (7-15 years) met the following inclusion criteria: (1) clinical manifestations of systemic small vessel involvement; (2) histological demonstration of pauci-immune necrotizing glomerulonephritis; and (3) serological findings of increased concentration of MPO-ANCA by ELISA te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
53
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 48 publications
12
53
0
Order By: Relevance
“…In the adult literature, it is reported that renal involvement in AAV can be so severe as to require dialysis-dependence in 23-60 % of these patients [15,16]. Our study found that 36 % of patients required dialysis at diagnosis, which is within the range previously reported in the pediatric literature as well [5,6,[10][11][12][13][17][18][19][20][21]. However, it is important to note that our study is based solely on those patients with renal involvement and does not include patients without renal involvement.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the adult literature, it is reported that renal involvement in AAV can be so severe as to require dialysis-dependence in 23-60 % of these patients [15,16]. Our study found that 36 % of patients required dialysis at diagnosis, which is within the range previously reported in the pediatric literature as well [5,6,[10][11][12][13][17][18][19][20][21]. However, it is important to note that our study is based solely on those patients with renal involvement and does not include patients without renal involvement.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to other childhood chronic diseases, children with AAV differ from adults in that they have a longer anticipated life span over which their disease must be managed. The peak age of onset of AAV in the pediatric population is during late childhood and adolescence, a critical time for growth as well as emotional, physical and reproductive development [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…As to prognosis, nine of 31 patients progressed to ESRD; of these nine patients, four required dialysis during the initial phase of therapy and did not recover renal function, three progressed to ESRD with episodes of relapse, and the remaining two progressed to ESRD without active disease or relapse [2]. Other studies have revealed that ANCA-associated GN progresses to renal failure in 20-40 % of patients; thus, it is important to identify patients with ANCA-associated GN and to manage treatment in the early stages of the disease [1,[3][4][5][6]. Our case was identified by SUS and was asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Although ANCA-associated GN is rare in childhood, there are a number of reviews of the clinical features and outcomes of pediatric ANCA-associated GN [2][3][4][5]. Hattori et al [2] reported that the clinical disease spectrum of ANCA-associated GN is similar in pediatric and adult patients and found that 29 % of patients with ANCAassociated GN progressed to end-stage renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation